Prediction model and experimental verification of coal and gas outburst shock wave based on Shock tube theory - Xuelin YANG; Guangcai WEN; Haitao SUN; Fazhi YAN; Huiming YANG; Jie CAO; Xiaoyang CHENG; Jun LU; Huhu LI (Meitan xuebao, 2024)
The coal and gas outburst process is frequently accompanied by strong dynamic effects, and the generating outburst shock wave will cause certain casualties, even damage ventilation facilities such as air doors, thus expanding the scope of accidents. In order to be close to the actual situation, a dynamic model of coal and gas outburst is established according to the phenomenon of on-site outburst process; Based on the theory of aerodynamics, the formation mechanism of one-dimensional shock wave in confined space is discussed. On this basis, the formation mechanism of outburst shock wave in the simulated roadway is clarified. It is pointed out that the high-speed gas flow sprayed into the roadway at the moment of outburst compresses air to form outburst shock wave, and the strength of outburst shock wave is determined by the gas expansion energy released during the acceleration phase of outburst gas flow; The prediction model of overpressure peak value of outburst shock wave based on gas pressure of outburst hole and diameter of outburst mouth is established. Using the simulation experiment system of coal and gas outburst impact dynamic effect and disaster characteristics, the simulation experiments of outburst dynamic effect under different gas pressure and coal loading were carried out. The experimental results show that the measured value of shock wave overpressure in the process of outburst simulation experiment is consistent with the theoretical value, which verifies the correctness of the theoretical model. When the coal loading is the same, the overpressure of outburst shock wave increases with the gas pressure; When the gas pressure is the same, with the increase of coal loading, the shock wave overpressure changes little. Under the same gas pressure, the diameter of outburst mouth will affect the magnitude of shock wave overpressure. When the diameter of outburst is small, the gas expansion energy released at the moment of outburst is small, resulting in small overpressure value of shock wave. Outburst shock wave strength \begin{document}$p'_2 $\end{document} and shock wave overpressure \begin{document}$\varDelta p' $\end{document} has a linear relationship with the ratio s1/s2 of the diameter of the outburst and the roadway. Therefore, gas pressure and outburst diameter are the main factors affecting the intensity of outburst shock wave. In addition, in the process of outburst simulation experiment, the overpressure of outburst shock wave in the simulated roadway is attenuated with the propagation distance. By analyzing the peak value data of shock wave overpressure in the roadway, it is found that the formula y=aΔPmaxx−1/2 can better describe the attenuation law of shock wave overpressure in the roadway. The outburst shock wave propagates to the end of the roadway and forms a secondary shock wave due to the reflection of obstacles. This study can provide guidance for scientific and rational design and arrangement of safety protection measures in outburst mines.